The prize and the price : shaping sexualities in South Africa - Steyn, Melissa E.; Van Zyl, Mikki (Cape Town, South Africa : HSRC Press, 2009)
"What is the prize, and who pays the price? The desired and the desi rable are often constellated through our ideas of what is undesired and undesirable, deeply knotted into our sense of self, our sense of where and how we fit into the world. These notions of desire form the backdr op to this powerful volume which examines the historical continuities a nd interruptions of heteronormativity in South African society. Leading and emerging scholars disentangle the strands of particular sexual ide ntities, and deepen the reader's understanding of the multiple workings of heteronormativity in South African society in particular, and sexua lity in general. Through analyzing where and how heteronormativity inte rsects with other axes of power and social identity, contributors to th is volume reveal that it is not monolithic, and heterosexuality as the South African norm is effectively 'outed' from within heteronormativity . The chapters extend beyond the well researched areas of sexuality - s ame sexualities, HIV/AIDS and gender-based violence - to less discussed areas, such as childhood sexuality and disability. The multiplicity of issues raised have relevance for a range of readers interested in the fledgling field of Sexualities Studies, and in its significance the sch olarship extends well beyond the borders of South Africa"--Cover.
Includes bibliographical references and index.
Keywords: Sex -- South Africa; Sexual orientation; Heterosexism -- South Africa